CONVERSION IN THE BIBLE: A DIALOGICAL PROCESS - Legrand, Lucien (Journal of Dharma, 2003)
When studying the topic of conversion in the Bible, we face a basic ambiguity at the outset. On the one hand, the vocabulary of conversion, frequent in the Scriptures, does not apply specifically to what we currently call conversion in the sense of a shift in religious affiliation. On the other hand, conversion in the usual sense given to the term nowadays is expressed by other terms in the Bible. This is not just a semantic observation. This ambiguity is significant. It invites us to reconsider what we call ‘conversion’ and possibly what we think to be conversion.